2004
DOI: 10.1080/16226510490439972
|View full text |Cite
|
Sign up to set email alerts
|

Phytoremediation of Arsenic-Contaminated Groundwater by the Arsenic Hyperaccumulating FernPteris vittataL.

Abstract: Arsenic concentrations in a much larger fraction of U.S. groundwater sources will exceed the maximum contaminant limit when the new 10 microg L(-1) EPA standard for drinking water takes effect in 2006. Thus, it is important to develop remediation technologies that can meet this new standard. Phytoremediation of arsenic-contaminated groundwater is a relatively new idea. In this research, an arsenic-hyperaccumulating fern, commonly known as Chinese Brake fern (Pteris vittata L.), was grown hydroponically to exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(49 citation statements)
references
References 17 publications
2
38
0
Order By: Relevance
“…Root structure under field conditions differs from that under greenhouse condition [43]. The success of phytoremediation, more specifically phytoextraction, depends on a contaminant-specific hyperaccumulator [45]. Understanding mass balance analyses and the metabolic fate of pollutants in plants are the keys to proving the applicability of phytoremediation [46].…”
Section: Vegetative Uptakementioning
confidence: 99%
“…Root structure under field conditions differs from that under greenhouse condition [43]. The success of phytoremediation, more specifically phytoextraction, depends on a contaminant-specific hyperaccumulator [45]. Understanding mass balance analyses and the metabolic fate of pollutants in plants are the keys to proving the applicability of phytoremediation [46].…”
Section: Vegetative Uptakementioning
confidence: 99%
“…However, routine analysis of As with NAA for the determination of As contamination or screening for As hyperaccumulators is invalid. Numerous studies have confirmed the As-hyperaccumulation property of the Chinese brake fern; however, little is known about the correlation between As and other elements in this fern (2)(3)(4)(5)(6)(7)(8)(9)(10)(11). Two experiments reported that K increased and Ca decreased in the fronds of the Chinese brake fern when As was added to the pots (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…Up to the present, there appears to be no cost-effective method for the in situ cleanup of Ascontaminated soils and groundwater. The Chinese brake fern (Pteris vittata L.) is a newly identified As hyperaccumulator and has proven potential in remediation of As contamination in soil and water (2)(3)(4). The fern has great ability for tolerance and accumulation of As; it can accumulate more than 1000 mg/kg As in its fronds when growing on the tailings with 23,400 mg/kg As in the field and soils spiked with 1500 mg/kg As in greenhouse conditions (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…The best way of long term strategy for improving phytoextraction is to understand and exploit the biological processes involved in metal acquisition, transport and shoot accumulation. This is due to higher concentrations level of heavy metal ions have inhibitory effects on plant metabolic activity, alternatively reduced growth of plants, leaf necrosis and inhibits the plant physiology systems [8].…”
Section: Relative Growthmentioning
confidence: 99%
“…As it has a high growth-rate, fibrous root system and broad leaves along with tendency to tolerate high metal concentration, it is considered as an important species to be used in phytoremediation [4,5]. Some macrophytes are found to remove different concentrations of arsenic ions, which make them suitable to act as bio-monitors for metals, and have ability to act as biological filters of the aquatic environment [6][7][8][9]. Arsenic is one of the most significant and priority pollutant which is found in natural and anthropogenic processes like weathering, biological activity, geochemical reactions, volcanic eruption, smelting of non-ferrous metals and burning of fossil fuels [10].…”
Section: Introductionmentioning
confidence: 99%